Vitis vinifera leaves towards bioactivity - Fernandes, Fátima (2013)
The majority of the works about Vitis vinifera L. (grape) focus their attention on wine or its major by-product, the grape pomace. Nevertheless, leaves of V. vinifera also constitute an important matrix of this agro-industry. In this study, the chemical composition and antioxidant potential of V. vinifera leaves from twenty Portuguese varieties (white and red) were evaluated for the ﬁrst time, concerning their reducing total capacity, reducing power and DPPH radical scavenging capacity. The phenolics presente in the aqueous extracts of V. vinifera leaves were trans-caffeoyltartaric and trans-coumaroyltartaric acids, myricetin-3-O-glucoside, quercetin-3-O-glucoside, quercetin-3-O-galactoside and kaempferol-3- O-glucoside, the last two compounds being the most predominant. Despite showing different activities proﬁles, all samples exhibited antiradical capacity against DPPH radical and reducing power in a concentration-dependent manner, with IC50 values below 800 g/mL. The obtained results are encouraging, increasing the possibility of taking proﬁt from the great wastes produced by the grapes processing industry.